Revision of Chassalia (Rubiaceae-Rubioideae-Palicoureeae) in Borneo, with 14 new species - Yu, Tian Yi; Turner, Ian M.; Cheek, Martin (European Journal of Taxonomy, 2021)
The genus Chassalia (Gentianales: Rubiaceae-Palicoureeae) in Borneo is revised based on a morphological survey of herbarium specimens using classical taxonomic methods. The tribal placement and probable paraphyly of Chassalia as currently delimited is reviewed. Previously, four described species of Chassalia were known from Borneo, with only one endemic species, Chassalia psychotriformis I.M.Turner nom. nov. (≡ Cephaelis psychotrioides Valeton). A key is given to the 18 species of the genus recognised from Borneo in this study. In total, 14 new species are described, all of them endemic to Borneo. These are: Chassalia atropurpurea T.Y.Yu sp. nov., Chassalia beamanii T.Y.Yu sp. nov., Chassalia calamus T.Y.Yu sp. nov., Chassalia chewii T.Y.Yu sp. nov., Chassalia involucrata T.Y.Yu sp. nov., Chassalia kinabaluensis T.Y.Yu sp. nov., Chassalia lancifolia T.Y.Yu sp. nov., Chassalia lancifolioides T.Y.Yu sp. nov., Chassalia longipes T.Y.Yu sp. nov., Chassalia macrocarpa T.Y.Yu sp. nov., Chassalia muluensis T.Y.Yu sp. nov., Chassalia muscicola T.Y.Yu sp. nov., Chassalia northiana T.Y.Yu sp. nov. and Chassalia ramosa T.Y.Yu sp. nov. Circumscriptions and discussions are given for all Bornean species recognised. A morphological glossary for Asian species of Chassalia is provided. Three separate species groups are recognised, the Chassalia curviflora and C. javanica groups, represented by a single species each in Borneo, and a new informal group, the ‘Involucrate group’, which is proposed and circumscribed to encompass the majority (16) of the Bornean species. Proposals for further work on Asian Chassalia are given.